2009
DOI: 10.2174/1874120700903010028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclic Strain and Growth Factors on Vascular Smooth Muscle Cell Responses

Abstract: Under physiological and pathological conditions, vascular smooth muscle cells (SMC) are exposed to different biochemical factors and biomechanical forces. Previous studies pertaining to SMC responses have not investigated the effects of both factors on SMCs. Thus, in our research we investigated the combined effects of growth factors like Bfgf (basic fibroblast growth factor), TGF-β (transforming growth factor β) and PDGF (platelet-derived growth factor) along with physiological cyclic strain on SMC responses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…21,22 The impact of strain amplitude on SMCs and their matrix production has been previously reported in several studies. 16,19,23,24 Less is known about the impact of strain frequency, especially on elastic matrix generation by SMCs cultured with EFs. Thus, in this study we systematically varied the cyclic stretch frequency to determine its impact on SMC proliferation, phenotype, and ECM production.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 The impact of strain amplitude on SMCs and their matrix production has been previously reported in several studies. 16,19,23,24 Less is known about the impact of strain frequency, especially on elastic matrix generation by SMCs cultured with EFs. Thus, in this study we systematically varied the cyclic stretch frequency to determine its impact on SMC proliferation, phenotype, and ECM production.…”
Section: Figmentioning
confidence: 99%
“…21,22 To date, most studies that applied cyclic stretch regimens have primarily used strain levels of > 2.5%, and a majority of them have used 10% strains. 16,19,23,24 However, other studies have shown that cellular synthesis and enzymatic activity of the elastolytic protease matrix metalloproteinase-2 (MMP-2) are increased at such high strains. 25,26 While MMP-2 plays an important role in matrix turnover and healthy reorganization, 25 chronic enzymatic activity can degrade newly synthesized elastic matrix and prevent its maturation and assembly within the scaffolds.…”
mentioning
confidence: 99%
“…The amplitude of cyclic strain which is dictated by the compliance of scaffolds has an anti-proliferative influence on VSMCs and also increases their apoptosis rate [46][47][48][49]. In addition, physiological cyclic strain upregulates synthesis of ECM products, such as collagen and elastin, which enhances the remodelling of vascular scaffolds [48]. On the other hand, it is necessary for cells within the scaffold to receive nutrients and discard waste material in order to maintain their viability, a property governed by interstitial fluid flow which is dependent on the scaffold permeability.…”
Section: Intimal Hyperplasia In Tissue Engineered Vascular Graftsmentioning
confidence: 99%
“…It has been shown that physiological cyclic strain (less than 15% amplitude) has an anti-proliferative influence on VSMCs and also increases the apoptosis rate of VSMCs (Colombo 2009;Chapman et al 2000;Morrow et al 2005;Kona et al 2009). In a recent in vitro study by Colombo (2009) which was dedicated to the study of the role of cyclic strain on VSMCs, bovine aortic smooth muscle cells were cultured under cyclic strain with varying mean and amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…The consistency of these findings on human VSMCs was also verified by conducting the same experiments on human Iliac VSMCs (Colombo 2009). Conversely, pathological values of cyclic strain (>15%) have been found to play a conflicting role and increase proliferation in VSMCs (Numaguchi et al 1999;Kozai et al 2005;Halka et al 2008;Kona et al 2009). In addition, physiological cyclic strain has been shown to upregulate gene expression for synthesis of ECM products such as collagen and elastin (Kona et al 2009).…”
Section: Introductionmentioning
confidence: 99%